Antenatal Depressive Symptoms and Neurodevelopment Outcomes in Children at 30 Months. A Study From South India - Thomas, Susan; Vigil, Emelia; Thomas, Tinku; Bellinger, David C.; Ramthal, Asha; Kurpad, Anura V.; Duggan, Christopher P.; Srinivasan, Krishnamachari (Frontiers in Psychiatry, 2020)
Background: Prevalence of antenatal depression in low and middle income countries is high. However studies examining the association between maternal antenatal depression and early childhood development from these countries are scarce. The objective of the study was to examine the association between antenatal depressive symptoms assessed serially during pregnancy and child neurodevelopment outcomes in mother –child dyads part of a randomized control trial of maternal B12 supplementation during pregnancy. Method: Subjects were 203 women who had participated in the placebo-controlled, randomized trial of vitamin B12 supplementation during pregnancy and 6 weeks post-partum on whom serial assessments of depressive symptoms in each of the trimesters were available. Cognitive, receptive language, expressive language, fine motor skills and gross motor skills were assessed at 30 months using the Bayley’s Scale of Infant Development- 3rd edition (BSID -III). Antenatal depressive symptoms were assessed at three trimesters using the Kessler’s 10 Psychological Distress Scale (K10). Women were classified into three categories: not depressed (K10 ˂6 in all trimesters), with intermittent depressive symptoms (K10 ≥6 in at least one trimester) and with persistent depressive symptoms (K10 score ≥6 in at least 2 trimesters). Results: 112 (55.2%) of the women did not have depressive symptoms, 58 (28.6%) had intermittent depressive symptoms and 33 (16.2%) had persistent depressive symptoms. The children of women with intermittent antenatal depressive symptoms scored lower on the receptive language domain on BSID-III compared to children of women who were not depressed on univariate analysis, but not on bivariate regression analysis. Women with persistent depressive symptoms had lower educational attainment (p=0.004), lower social support (p=0.006) and used more emotional coping strategies (p=0.005) compared to the not depressed group. Conclusions: A significant number of women in south India had antenatal depressive symptoms. Findings from this study suggest a possible association between antenatal depressive symptoms and receptive language in children. Larger studies including women with clinical depression are needed to confirm these findings.